Issues of Exhibiting the Armenian Traditional Dwelling in the Memorial Complex of Sardarapat’s Battle, National Museum of Armenian Ethnography and History of the Liberation Struggle - Yeritsyan, Karine (History and Culture, 2022)
Issues of exhibiting the armenian traditional dwelling in the museum of Armenian ethnography. The article focuses on peculiarities of the dwellings of the ethnic group that has lived in the Armenian Highland. Special attention is drawn to the conditions of construction of traditional folk dwellings. The peculiarities of the skylight dwellings construction and the prevalence of its two variations in the historical and ethnographic regions of Armenia are also noteworthy. Glkhatun was the main type of dwelling in the second half of the 19th -early 20th centuries. The article also discusses the impact of the Soviet period on the traditions of house building and the main changes as a result of this impact. The role of museums in the preservation of cultural values is emphasized. The relevance and significance of exhibiting traditional houses in museums are also studied. Variants for displaying dwellings are being considered. The article touches upon the issue of organizing an exhibition of a traditional dwelling in the Museum of Armenian Ethnography.